miR-142-3p Modulates Cell Invasion and Migration via PKM2-Mediated Aerobic Glycolysis in Colorectal Cancer - JunYu Ren; Wenliang Li; Guoqing Pan; Fengchang Huang; Jun Yang; Hongbin Zhang; Ruize Zhou; Ning Xu (Analytical Cellular Pathology)
Decreased expression of miR-142-3p was observed in human cancers. However, the function and mechanism of miR-142-3p in human colorectal cancer remain obscure. The expressions of miR-142-3p in human colorectal cancer tissues and cell lines were measured by RT-qPCR. The effects of miR-142-3p on cell invasion and migration were detected by transwell assays. The efficiency of aerobic glycolysis was determined by glucose consumption and lactate production. Dual-luciferase reporter assays were performed to confirm the correlation between miR-142-3p and pyruvate kinase isozyme M2 (PKM2). The level of PKM2 was assessed by western blotting. Our results showed that the expression of miR-142-3p was decreased both in human colorectal cancer tissues and in cells. Overexpression of miR-142-3p in cell line attenuated colorectal cancer cell invasion and migration. About the underlying mechanism, we found that miR-142-3p modulated aerobic glycolysis via targeting pyruvate kinase M2 (PKM2). In addition, we demonstrated PKM2 and PKM2-mediated aerobic glycolysis contributes to miR-142-3p-mediated colorectal cancer cell invasion and migration. Hence, these data suggested that miR-142-3p was a potential therapeutic target for the treatment of human colorectal cancer.